Surgical Navigation for Malignancies Guided by Near‐Infrared‐II Fluorescence Imaging. Issue 3 (18th January 2021) - Yang, Rui‐Qin; Lou, Kang‐Liang; Wang, Pei‐Yuan; Gao, Yi‐Yang; Zhang, Yong‐Qu; Chen, Min; Huang, Wen‐He; Zhang, Guo‐Jun
Abstract: Near‐infrared (NIR) fluorescence imaging is an emerging noninvasive imaging modality, with unique advantages in guiding tumor resection surgery, thanks to its high sensitivity and instantaneity. In the past decade, studies on the conventional NIR window (NIR‐I, 750–900 nm) have gradually focused on the second NIR window (NIR‐II, 1000–1700 nm). With its reduced light scattering, photon absorption, and auto‐fluorescence qualities, NIR‐II fluorescence imaging significantly improves penetration depths and signal‐to‐noise ratios in bio‐imaging. Recently, several studies have applied NIR‐II imaging to navigating cancer surgery, including localizing cancers, assessing surgical margins, tracing lymph nodes, and mapping important anatomical structures. These studies have exemplified the significant prospects of this new approach. In this review, several NIR‐II fluorescence agents and some of the complex applications for guiding cancer surgeries are summarized. Future prospects and the challenges of clinical translation are also discussed. Abstract : Compared with traditional near‐infrared (NIR‐I) fluorescence imaging, NIR‐II imaging modality can significantly improve imaging penetration depth, spatial resolution, and inadequate signal‐to‐noise ratios. A variety of NIR‐II luminescent materials and imaging systems are developed, and widely applied to guide the surgery for malignancies in preclinical stage. Also, preliminary clinical translation is achieved, showing promising application prospects.